The Effect Of Tax Socialization And Mobile Samsat Services On Motor Vehicle Taxpayer Compliance At SAMSAT Sumedang Regency - Erpi Rahman; Ai Anita Karolina (Journal of Business, Accounting and Finance, 2023)
Problems related about Taxpayer Compliance still often arise, especially regarding to Motor Vehicle Taxes. Therefore, the efforts are needed to improve taxpayer compliance, one of which is the Socialization of Taxation and Mobile Samsat Services. This present study aims to determine partially and simultaneously the effect of Tax Socialization and Mobile Samsat Services on Motorized Vehicle Taxpayer Compliance. This research employed quantitative approach. The number of research samples was 100 respondents using the Simple Random Sampling method. The analysis used is multiple linear Keywords: Tax Socialization, Mobile Samsat Service, Taxpayer Compliance. Corresponding Author: Ai Anita Karolina1, Prodi Akuntansi, regression analysis. Data processing using the IBM SPSS 25 program. The results showed that the Socialization of Taxation and Mobile Samsat Services had a simultaneous and signifi cant effect on the Compliance of Motor Vehicle Taxpayers at SAMSAT Sumedang Regency. This is indicated by the regression equation Y =16,350 +0,142. + 0,509. The result of the coefficient of determination test to determine the amount of contribution given by the Socialization of Taxation and Mobile Samsat Services to the Compliance of Motor Vehicle Taxpayers is 55.1%. Furthermore, according to the results of the t-test, Tax Socialization has no effect on taxpayer compliance < (1,561<1,985). Meanwhile, Mobile Samsat Service has a significant effect on Taxpayer Compliance as seen from > (5,452>1,985).